MANAJEMEN PENDIDIKAN ISLAM : KONSEPSI DAN AKTUALISASI KEPEMIMPINAN TRANSFORMASIONAL DI LEMBAGA PENDIDIKAN ISLAM - Afriyanto, Andre; Khoiri, Nur (JS (JURNAL SEKOLAH), 2024)
Abstract : This research aims to explain the conception and actualization of Transformational Leadership in Islamic educational institutions. The transformational leadership of school/madrasah principals emphasizes their efforts to influence their subordinates, especially teachers, in order to gain support from various stakeholders in improving the quality of student education. The method used in the preparation of this article is the Literature Study method. Literature Study is a data collection method that aims to search for information and data through written documents or online sources that support the writing process. Based on the research findings and discussions in this study, several conclusions can be drawn. One of them is that transformational leadership is a type of leadership that can bring about change within individuals and the entire organization to achieve higher performance and outcomes. To become a transformational leader, several approaches can be taken, including: a) Creating a clear vision, b) Managing the implementation of the vision to establish a clear vision, c) Motivating the team, d) Being creative and innovative.Keywords : Leadership, Transformational, EducationAbstrak : penelitian ini bermaksud untuk menerangkan bagaimana konsepsi dan aktualisasi Kepemimpinan Transformasional di lembaga pendidikan Islam. Kepemimpinan transformasional kepala sekolah/madrasah menekankan upaya mereka untuk mempengaruhi bawahannya, terutama guru, guna mendapatkan dukungan dari berbagai pihak dalam meningkatkan kualitas pendidikan siswa. Metode yang digunakan dalam penyusunan artikel ini adalah metode Studi Pustaka. Studi Pustaka adalah metode pengumpulan data yang bertujuan untuk mencari informasi dan data melalui dokumen tertulis atau sumber online yang mendukung proses penulisan. Berdasarkan penelitian ini, disimpulkan bahwa kepemimpinan transformasional memiliki kemampuan untuk menginspirasi perubahan dalam individu-individu yang terlibat serta dalam keseluruhan organisasi, dengan tujuan meningkatkan kinerja dan hasil secara signifikan. Untuk menjadi seorang pemimpin transformasional, ada beberapa langkah yang dapat diambil, seperti mengembangkan visi yang jelas, mengelola implementasi visi tersebut, memotivasi tim, dan menunjukkan sikap kreatif serta inovatif.Kata Kunci : Kepemimpinan, Transformasional, Pendidikan